Sintesis Konseptual Prinsip-Prinsip Dasar Total Quality Management (TQM) dalam Manajemen Pendidikan: Sebuah Tinjauan Literatur Terintegrasi - Krisna Aditiya Wibowo; Romi Faslah (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
In the era of digital disruption, Islamic Education (PAI) institutions face complex challenges in maintaining relevance and the quality of graduates. This research aims to synthesize the fundamental principles of Total Quality Management (TQM) and integrate them into the context of future-oriented Islamic education management. The research method used is qualitative with a library research approach, where data were collected through accredited scientific literature and analyzed using content analysis and theoretical synthesis techniques. The results indicate three main pillars in the implementation of TQM in Islamic educational institutions: 1) Reconceptualization of customer focus, which positions students as a divine "Amanah" (trust) whose potential must be developed to the maximum; 2) Implementation of a continuous improvement cycle through the Plan – Do – Check - Act (PDCA) model, which is viewed as a manifestation of the values of Itqan (professionalism) and Muhasabah (self-evaluation); 3) Synergy of total involvement and visionary leadership based on the principles of Syura (consultation) and Uswah Hasanah (exemplary leadership). This research concludes that the success of TQM in PAI is an orchestration between data-driven professional management and spiritual integrity. These findings provide a theoretical contribution to educational institution managers in building a resilient, authentic quality culture amid global competition.   Keywords: Total Quality Management (TQM), Education Management, Educational Quality, PDCA.